Rancang Bangun Aplikasi Penentuan Harga Pokok Produksi pada CV Langganan - Diana, Raysa Machfud; Widodo, Arifin Puji; Sutanto, Teguh (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
CV Langganan is a manufacturing company in West Jakarta area that has existed since 2001. The company is engaged in the production of jewelry made from gold and gems. The production process is done when the stock in the store has been sold, the jewelry products produced have different specifications between each other. In the process of making jewelry there must be costs incurred by the company, the cost is often known as the cost of production. But now the company in determining the cost of production has not been based on the three elements of the cost of production, namely the cost of raw materials, direct labor costs, and factory overhead costs. This resulted in the company having difficulty knowing the value of the profit earned and can not determine the selling price of the product. Based on the impact of existing problems, the company can apply the calculation of cost of production by using the full costing method. By using this method the company can calculate all the elements of production cost into the cost of goods. Based on the results of tests conducted on the application built, states that this application has been able to produce a report on the cost of production.Keywords: Full Costing, Cost of Production, Cost Accounting